Influência do horário de realização do exercício resistido sobre a resposta cardiovascular de idosas hipertensas - MENDES , Pauliana Conceição (2019)
Introduction: Physical exercises are recommended to be used in the physical training programs of hypertensive patients. However, there are still few studies analyzing the time of the training session and cardiovascular responses in medicated hypertensive patients. Objective: To evaluate the influence of resistance exercise time / shift on the magnitude of cardiovascular response in hypertensive elderly women. Methodology: The study objectives were presented and the Informed Consent Form (ICF) was signed, as well as the application of the anamnesis questionnaires, the International Physical Activity Questionnaire (IPAQ) and the Physical Activity Questionnaire (PAR). -Q). At 24-hour interval, body composition (weight, height, body mass index (BMI)) and familiarization were evaluated. The 10-Hour Max Repetition (RM) Test with 48 h recovery was continued to perform the 10RM retest. At 48 h intervals, resistance exercise protocols were performed in the morning or afternoon, performed randomly and 7 days apart between each protocol. Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), Heart Rate (HR), Mean Blood Pressure (MAP), Dual Product (SD), Pulse Pressure (PP), and Heart Rate Variability (HRV) values were collected before (pre-exercise) and 10 minutes after the experimental protocols. Statistical analysis: Data normality was initially tested by the Kolmogorov Smirnov normality test. For hemodynamic data, Wilcoxon test with Bonferroni post test was performed to analyze SBP, DBP, HR, MAP, SD, and PP in the different. For the analysis of Heart Rate Variability (HRV) in the morning: Student's t test was applied for the variables Mean RR, STD RR (SDNN), RMSSD, HF and Wilxcoxon in the LF variable. In the afternoon: Student's t test was applied to Mean RR, STD RR (SDNN) variables; Wilcoxon test with Bonferroni post test in the LF variables and LF / HF ratio and Mann Whitney test in the HF variable. All results were represented by the original values, which are expressed as Mean ± Standard Deviation of Mean (M ± SDM). A significance level of 5% (p≤0.05) was adopted. Analyzes were performed using the GraphPad Prism statistical package, version 7.0. Results: The main findings revealed that there was no significant difference in hemodynamic and autonomic nervous system variables, either in the morning or in the afternoon. Conclusion: The period of resistance exercise does not alter the cardiovascular responses in medicated hypertensive elderly women.